(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Warmth is a key consideration for consumers when choosing products. Existing research has mostly focused on testing the warmth performance of down products in a horizontal state, neglecting the non-horizontal state during actual wearing. This study investigates the thermal insulation performance of down waddings under different placement conditions and their interrelationships. Four types of stitching spacing and five types of unit filling amounts are determined through market research, and 20 pieces of down waddings are made. Thermal resistance experiments are conducted in both horizontal placement and 24-hour suspension states. The experimental results show that under 24-hour suspension, the thermal resistance value of down waddings generally decreases; Under the same stitching spacing conditions, the unit filling amount corresponding to the maximum thermal resistance value in the 24-hour suspension state has decreased; There is a significant difference in thermal resistance values between the two placement states, with a Pearson correlation coefficient of 0.939, indicating a strong positive correlation; A mathematical regression model y=0.825x + 0.033 is established through SPSS analysis to describe the relationship between the thermal insulation of down wadding in two different placement conditions. The findings of this study provide an important theoretical basis and practical guidance for further research, design, and production of down products.